DERECHO DE VISITAS – DERECHO Y DEBER DE COMUNICACIÓN - CONFLICTOS POS DIVORCIO INTERFACE JURIDICO PSICOLOGICA - Vázquez, Oscar (European Scientific Journal, ESJ, 2015)
The height of the psychological legal interface occurs in family law and particularly in visiting arrangements (contact and communication between parents and children). This is because it is the Reggia way of developing productive relationships. It is accomplished by mainly accepting others as they are, such that they both have value today in relation to the treatment of domestic violence and gender. The concept of man as an imperfect father and the woman as an imperfect mother are conditions which fosters the development of an image of healthy parental couple. The challenge for professionals involved in decisions that affect the daily lives of people as in the case of visiting arrangements, is to assume the responsibility to do. They consider not only the uniqueness of each human being, but also the children as an axis of communication with emotionally significant people. A Judges decision requires interdisciplinary support for the valuation of children resources to establish their evolving capabilities. The access of children to familiarly significant others is a human right, and as such, is a source of mental health for children. Psychologists working as part of the interdisciplinary teams of the courts are very important, and that their interventions must be tailored in the context of the child, family, and society. By this, they develop and mainly adapt to the context of the institution of attendance from which they obtain their expertise.